The Weight of Words - Metzger, Laurent (Journal of Modern Languages, 2017)
This study attempts to maintaine that, while we cannot dismiss the written word, which is part and parcel of our history, we have to analyse the spoken word and assess how important it is in our present society. The paper believes that oral words are prominent. It also seeks to analyse the consequence of utterances, and to make an attempt to unravel the links which exist and which may be established between the written and the oral words as well.